Study on the impact of central environmental protection inspection on the health of the older adult population—A quasi-natural experiment in China - Yang, Jiayu; Deng, Juqiu; Ye, Lianguang; Liu, Li; Hu, Xiuying (Frontiers in Public Health, 2024)
In 2015, the central government of China established the Central Environmental Protection Inspection (CEPI) system for oversight of local governments. It enhanced local government enforcement of environmental regulations, which had a considerable influence on the health of the local elderly population. This study quantifies the effects of local government regulation brought about by CEPI on the health of the elderly. It examines the impact mechanism using the DID model and panel data from the China Health and Retirement Longitudinal Study (CHARLS). The results show that: (1) local governments' environmental protection regulations implemented by CEPI have a positive impact on the elderly' general health. The results of the study passed the parallel trend test, PSM test, replacement variable test and placebo test, and remained significant; (2) in terms of the impact mechanism, CEPI has promoted local governments' environmental governance initiatives, which has reduced industrial wastewater emissions, industrial sulfur dioxide emissions, and industrial fumes emissions. This has improved air-quality, thereby creating a good living environment for the elderly and improving their overall health; (3) according to heterogeneity research, the health of elderly living in Yangtze River Basin, urban elderly, and elderly without chronic diseases is more significantly affected by environmental protection regulations of local governments brought about by CEPI.